Gotham City sirens strange fruit - Bedard, Tony.; Calloway, Peter 1982-.; Guinaldo, Andres; Haun, Jeremy; March, Guillem 1979-. (New York DC Comics, 2011)
"Catwoman deals with the aftermath of battling her sister in this new title collecting issues #14-20 of the monthly series. Secrets from the 'Return of Bruce Wayne' storyline affect all three Sirens, setting them against each other in a brutal display of their villainous roots. And don't miss guest appearances by Zatanna and Talia al Ghul"--Publisher's web site.
Originally published in single magazine form in Gotham City Sirens 14-19--T.p. verso.
Keywords: Graphic novels